Fetomaternal outcome following labour induction in oligohydramnios and borderline liquor: a retrospective study in a tertiary care hospital - Thomas, Jyothi Susan; Daniel, Mary; Selvaraj, Sangeetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Amniotic fluid provides a protective milieu for the growing fetus in pregnancy and labour. A decrease in the amniotic fluid volume has been associated with increased maternal morbidity and fetal morbidity and mortality. The purpose was to compare the effect of labour induction on the fetomaternal outcome in women with oligohydramnios, borderline liquor and normal liquor at term. Methods: A retrospective study of all the labour induction in women with oligohydramnios, borderline liquor and normal liquor volume at 37-42 weeks gestation in a tertiary care teaching hospital. The demographic characteristics, maternal outcomes like mode of delivery, indication for operative delivery, meconium stained liquor and perinatal outcomes were compared in between the three groups. Parametric data was compared by chi-square test and non-parametric data by students’-test. A p-value less than 0.05 was taken as significant. Results: Among the 2338 deliveries during the study period, labour was induced in 266 women (11.3%). Out of which, 109 cases (40.9%) in oligohydramnios group, 111cases (41.7%) in borderline liquor group and 46 cases in normal liquor group. The incidence of meconium stained liquor, the number of operative deliveries and fetal distress was significantly higher and significantly lower birth weight (<2.5 kg) in the group with oligohydramnios and borderline liquor (p <0.05). Low Apgar score and admission to neonatal intensive care unit was higher in the oligohydramnios group (p<0.05). Conclusions: Induction of labour on detecting borderline liquor at term may help in reduction of maternal and fetal morbidity and mortality.